Effectiveness and safety of a modified (rib ends fixed under transverse process) thoracoplasty for rib hump deformity in adults with severe thoracic scoliosis: A retrospective study. Issue 39 (25th September 2020) - Yu, Bin; Zhao, Deng; Wang, Fei; Hu, Zhengjun; Zhong, Rui; Zhao, Hehong; Liang, Yijian
Abstract : Abstract: Razor back deformity is one of the most noticeable problems of severe scoliosis. Thoracoplasty has been reported to be a useful approach to correct the rib hump deformity. However, the outcomes of thoracoplasty in patients with severe, rigid, thoracic scoliosis have not yet been evaluated. To evaluate the effectiveness and safety of a modified technique of thoracoplasty (rib ends fixed under transverse process) for rib hump deformity in adults with severe thoracic scoliosis and severe pulmonary dysfunction. Patients with severe thoracic scoliosis and severe pulmonary dysfunction who underwent staged surgical strategy including halo-pelvic traction, spinal osteotomy combined with the modified thoracoplasty were included. To avoid paradoxical breathing result from multiple rib resections and enlarge the capacity of thoracis, the ends after rib resection were fixed under transverse process compared with conventional thoracoplasty. Patients were excluded on the basis of pulmonary diseases and inadequate follow-up. Data on deformity correction and pulmonary complications were reviewed. A t test was performed on the pre- and postoperative data of pulmonary function, height of the rib hump deformity, and total lung area. Eighteen patients (5 men and 13 women) with a major thoracic curve of >130° were included. The mean age of patients was 25.3 ± 3.6 years (range, 19–32 years), with an average length of follow-up of 30.2 months. After application of halo-pelvic traction, the mean major thoracic curve decreased from 168.2° ± 14.28° to 97.3° ± 10.75° and the thoracic kyphosis decreased from 159.4° ± 20.60° to 94.8° ± 9.58°. On average, 6.3 (range, 4–8) ribs were resected. The height of the rib hump decreased from 84.6 ± 13.3 to 15.3 ± 3.4 mm. The average predicted forced vital capacity (FVC%) before surgery was 37.2 ± 13.30%, indicative of severe pulmonary impairment, with a small but non-significant improvement in the FVC% at the final follow-up. The mean total lung area increased from 2583.2 ± 501.36 to 2890.1 ± 537.30 mL at the last follow-up. No severe pulmonary complications occurred. Our modified approach to thoracoplasty procedure is effective and safe in correcting a razor back deformity in patients with severe, rigid, scoliosis, and severe pulmonary dysfunction, without causing any significant change in long-term pulmonary function.